Conceptual Transformations of Public Diplomacy - M. M. Lebedeva (Vestnik MGIMO-Universiteta)
Abstract: In the 1960s when it first appeared as a concept public diplomacy was defined very broadly as the impact of a state on a foreign audience. In the 21st century changes in the political organization of the world have led to the strengthening of the social power a state, as well as to the expansion of the means and methods of its use to influence foreign audiences. A new state practice was developed – state policy in the field of international communication. Public diplomacy is only one of the directions of this policy. However, as a result of the initially very broad definition of public diplomacy, it has come to be identified in scientific literature with propaganda, strategic communication, and national branding. The tools developed in related fields – military, commercial – has its own specifics. The article shows that association of these activities with public diplomacy is wrong both in theoretical and practical terms, since it does not allow choosing the appropriate tools of influence for a specific situation. It is argued that under public diplomacy it is still advisable to understand such state communication with a foreign audience, which, firstly, is based on creating attractiveness, secondly, which is focused specifically on the political sphere, and thirdly, it involves dialogue. Comparative analysis of public policy in the field of international communication from different spheres will allow us to better understand the specifics and mechanisms that work in each of these areas. In the middle of the 20th century, non-state actors had not yet entered the international arena en masse, and structures that were “trackers” of state policy were included in public diplomacy in its unofficial channels. Today the situation is much more complicated: along with “trackers” within the framework of unofficial channels of public diplomacy, there are actors of world politics who have significant independence in the world arena and often pursue state policy at their own discretion. As a result, there is often a duplication of certain points, which may be perceived by the external audience as annoying, and on the contrary, there may be contradictions in the actions of various actors of the same state. In any case, in order to somehow reduce such negative effects, it is necessary to study the activities of non-state actors (first of all, actors, and not just “trackers”) of public diplomacy. Also, International Relations (in contrast to other fields of political science) does not study official channels of public diplomacy, including briefings for journalists by various state officials, especially interaction with an external audience through websites, social networks, etc. It is obvious that this subject area should attract the attention of researchers of International Relations to a greater extent than it is observed today.